Effectiveness of KASP-SNP markers in selecting for grain quality traits in rice - Asante, Maxwell Darko; Ofosu, Kirpal Agyemang; Frimpong, Felix; Alphonso, Deladem Kwami; Nartey, Elizabeth; Obeng, Agyei Elvis; Bam, Ralph K.; Gamenyah, Daniel D.; Ribeiro, Priscilla F.; William, Harindra Manilal (Elsevier, 2025)
Grain quality is a crucial factor for rice consumers, and as such, it is a major focus for breeders. Phenotyping for grain quality traits can be a laborious and costly process. In this study, we evaluated the effectiveness of KASP-SNP markers in selecting for grain quality traits, including aroma, gelatinization temperature, grain length, grain width, and grain length: width ratio. We phenotyped 300 diverse rice genotypes for these four traits and genotyped them using their respective KASP-SNP markers. A regression analysis of the phenotype on the genotype was performed. The markers associated with the fgr-1 and GS3 genes explained 97 % and 94 % of the phenotypic variation for aroma and grain length, respectively. Two SNP markers (snpOS00440 and snpOS00441) associated with the GW5/SW5 gene each explained 82 % of the phenotypic variation for grain width, which increased marginally to 85 % when combined. However, two markers, snpOS00036 and snpOS00450, for gelatinization temperature explained only 2 % and 25 % of the phenotypic variation, respectively, indicating that these markers were not efficient in predicting this trait. Our findings suggest that the markers associated with aroma (fgr-1), grain length (GS3), and grain width (GW5/SW5) are highly efficient and reliable for marker-assisted selection.